2011
DOI: 10.7759/cureus.32
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Radiosurgery (CyberHeart™) for Treatment of Arrhythmia: Physiologic and Histopathologic Correlation in the Porcine Model

Abstract: Objectives: This porcine pre-clinical investigation sought to demonstrate a new and novel application for radiosurgery, the ablation of cardiac arrhythmias. Pre-clinical studies in the porcine animal model were used to investigate the accuracy with which the pathological region in the heart that is routinely treated for atrial fibrillation could be targeted with radiosurgery. Pathologic and electrophysiologic (EP) changes resulting from radiosurgical ablation were used as primary study endpoints.Methods: Two H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 18 publications
0
36
0
Order By: Relevance
“…Although the authors claimed that both 25 Gy and 35 Gy in a single fraction can lead to electrical block and transmural fibrosis, only data for the 35 Gy treatment were shown. A third publication by Zei et al [37] presented the same data as in Maguire et al [32] with the additional data of RA/CRS targeted to the pulmonary veins in 17 canines. The authors found treatment effects for doses between 15 and 35 Gy during electrophysiology studies and gross pathological analysis [37].…”
Section: Preclinical/animal Studies For Cardiac Radiosurgerymentioning
confidence: 88%
See 3 more Smart Citations
“…Although the authors claimed that both 25 Gy and 35 Gy in a single fraction can lead to electrical block and transmural fibrosis, only data for the 35 Gy treatment were shown. A third publication by Zei et al [37] presented the same data as in Maguire et al [32] with the additional data of RA/CRS targeted to the pulmonary veins in 17 canines. The authors found treatment effects for doses between 15 and 35 Gy during electrophysiology studies and gross pathological analysis [37].…”
Section: Preclinical/animal Studies For Cardiac Radiosurgerymentioning
confidence: 88%
“…Finally, we added initial technical, pre-clinical, and clinical manuscripts not covered by the search based on our own experience in cardiac radiosurgery in the past 12 years. Evidence was finally extracted from the remaining 42 manuscripts, which include reports on two clinical trials [22,23], two clinical case series [24,25], eight case reports [19,20,[26][27][28][29][30][31], eight preclinical studies [18,[32][33][34][35][36][37][38][39], fourteen technical studies [40][41][42][43][44][45][46][47][48][49][50][51][52][53], and eight reviews or opinions [7,[54][55][56][57][58][59][60].…”
Section: Clinical Trial and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The two reported human phase I studies have prescribed a potentially safe 25 Gy for cardiac ablation of ventricular tachycardia, 8,9 while the most recent animal studies for AF suggested that doses over 30-32.5 Gy might be needed for the treatment to be effective. 5,7 The transferability of the animal results to human treatment, however, remains unclear.…”
Section: Discussionmentioning
confidence: 99%